On network models and the symbolic solution of network equations - Reinschke, Kurt (Zielona Góra: Uniwersytet Zielonogórski)
This paper gives an overview of the formulation and solution of network equations, with emphasis on the historical development of this area. Networks are mathematical models. The three ingredients of network descriptions are discussed. It is shown how the network equations of one-dimensional multi-port networks can be formulated and solved symbolically.
Keywords: history of network theory; network graphs; network equations; modified nodal analysis; admittance representation of multi-ports; multidimensional networks